2019
DOI: 10.1016/j.ijid.2019.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Predicting congenital rubella syndrome in Japan, 2018–2019

Abstract: A B S T R A C TObjectives: A rubella epidemic has been ongoing in Japan since August 2018. In the present study, we aimed to predict the likely size of a congenital rubella syndrome (CRS) epidemic during 2018-19. Methods: The expected number of CRS cases was estimated using an integral equation based on agespecific incidence of rubella among adult women, the time delay from gestational age of infection to diagnosis of CRS, and distribution of the mothers' age at delivery. We used epidemic data during 2012-14 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 29 publications
1
10
0
1
Order By: Relevance
“…A study in Japan in 2018 showed that the prevalence of congenital rubella infection was 9.5% [17]. Where as our study showed 4.9% of CRS in the three years period with estimated 7 confirmed cases of congenital rubella syndrome.…”
Section: Discussionsupporting
confidence: 60%
“…A study in Japan in 2018 showed that the prevalence of congenital rubella infection was 9.5% [17]. Where as our study showed 4.9% of CRS in the three years period with estimated 7 confirmed cases of congenital rubella syndrome.…”
Section: Discussionsupporting
confidence: 60%
“…The present study investigated the risk of a rubella epidemic by geographic region in Japan. On the basis of the spatial datasets of age-specific seroepidemiological surveys and the number of foreign travelers, the effective reproduction number was computed with data from 10 different geographic regions (Figure 1), using the nationwide estimate of the age-and sexdependent next-generation matrix parameterized and quantified in a previous study (Kayano et J o u r n a l P r e -p r o o f al., 2019). The populations of susceptible adult males were concentrated in urban regions ( Figure 4B), and those regions also had a greater number of foreign travelers ( Figure 4A), which contributes to a synergized effect resulting in a greater risk of exposure to untraced cases of rubella.…”
Section: Discussionmentioning
confidence: 99%
“…There was an epidemic from 2012 to 2014 involving more than 12,000 confirmed cases that were dominated by adult males aged 30–59, and there were as many as 45 confirmed CRS cases during the epidemic ( Kinoshita and Nishiura, 2016 , Kayano et al, 2019 ). A similar outbreak recurred in 2018–2019, also involving CRS cases ( Lee et al, 2019 ), which finally compelled the Japanese government to implement a supplementary immunization program for adult males ( Ministry of Health, Labour and Welfare, 2019 , Ujiie, 2019 ). As a result of the 2018–2019 epidemic, more than 5,000 confirmed cases were reported to the National Institute of Infectious diseases, with the majority of cases observed in urban areas and especially among adult male aged 35-64 years, a slightly elevated ages of cases compared with 2012-14 epidemic ( Ministry of Health, Labour and Welfare, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to modelling the epidemiological dynamics of rubella, we have also devised a model to anticipate CRS from rubella in pregnant mothers. To do this, we used rubella data in adult females, demographic data of livebirths and the distribution of mothers’ ages at delivery, and a precise version of the predictive model can be found elsewhere [17]. In the present study, we used the CRS prediction model to anticipate the cumulative incidence of CRS under various SIP scenarios, and the quantified model predicted the same count (i.e., 45 cases) of CRS from 2012–2014.…”
Section: Discussionmentioning
confidence: 99%
“…That is, our subject ages were grouped as 0–4, 5–9, 10–14, 15–19, 20–24, 25–29, 30–34, 35–39, 40–44, 45–49, 50–54, 55–59, 60–64, 65–69 and ≥70 years old, that is, in total, there were 15 age groups ( n a = 15). In addition to the analysis of rubella case data, we predicted the number of CRS cases using the expected number of rubella cases in adult females [17]. To do so, we analyzed not only rubella case data, but also the vital statistics associated with child delivery.…”
Section: Methodsmentioning
confidence: 99%